Diversity of Ethiopian Durum Wheat Landraces for Resistance to Stem Rust Seedling Resistance Genes - Silas Chiko; Mesfin Kebede Gessese; Daniel Shimelash; Wondimeneh Taye Haile; Belay Yebo Melo; Adera Sisay Wassie; Zemach Sorsa Lakore; Fentanesh Chekole Kassie (Advances in Agriculture)
Stem rust caused by Puccinia graminis f. sp. tritici (Pgt) is one of the most important diseases of wheat worldwide. Breeding for resistance to diseases is the most important approach for mitigation of yield losses. This study was conducted to estimate the diversity of all stage stem rust resistance (ASR) genes on the 142 durum wheat landrace accessions at seedling stage. The study was conducted in greenhouse at Ambo Plant Protection Research Center on the 142 durum wheat landrace accessions using 20 differential lines, one susceptible line (McNair), and eight Pgt races. The result depicted the presence of Sr7b, Sr8a, Sr9b, Sr10, Sr11, Sr13, Sr17, Sr30, Sr31, Sr36, and SrTmp in the Ethiopian durum wheat accessions. Among the 142 durum wheat accessions, 83 accessions were identified for possessing single ASR genes, and four accessions including the universal susceptible line (McNair) did not have effective resistance genes to the pathogen races tested in this study. The remaining 55 accessions had either a combination of two resistance genes, unknown number and kind of genes, or unidentified genes displaying resistance across all the pathogen races. This study demonstrated the prevalence of significant genetic diversity for stem rust ASR genes in the Ethiopian durum wheat landraces.